2022
DOI: 10.1007/s10597-022-01004-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis Early Intervention Across the Life Span: A Service Perspective

Abstract: Previously youth-orientated, UK early intervention in psychosis (EI) services expanded care in 2016 to adults of any age. To compare EI care offering, clinical characteristics, and potential benefits for under-35s and over-35s, an observational study considering anonymised data for users of London-based EI services between April 2016 and December 2019 was conducted. Descriptive statistics and between groups comparisons are reported. The analysis considered 692 service users (32.5% over-35). Over-35s were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Consistent with the general population, women appeared to have a higher education (Istituto Nazionale di Statistica Istat 2021 ). Our findings are consistent with the largest incidence study conducted in Europe (Jongsma et al 2018 ) that found the incidence of treated SSD in women peaks in their 50s compared to men in their 20s and that most individuals who had their FEP after the age of 35 were women (Taylor et al 2023 ). Our findings are also consistent with the widely accepted observation that women have a less severe clinical profile at presentation, which can in turn result in delayed diagnosis (Ferrara and Srihari 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the general population, women appeared to have a higher education (Istituto Nazionale di Statistica Istat 2021 ). Our findings are consistent with the largest incidence study conducted in Europe (Jongsma et al 2018 ) that found the incidence of treated SSD in women peaks in their 50s compared to men in their 20s and that most individuals who had their FEP after the age of 35 were women (Taylor et al 2023 ). Our findings are also consistent with the widely accepted observation that women have a less severe clinical profile at presentation, which can in turn result in delayed diagnosis (Ferrara and Srihari 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…There is a need for a call for action to develop and deliver more sex- and gender-sensitive treatment programs across the globe ( 91 , 92 , 93 ) as a first step in personalized treatment programs ( 94 ). We believe that the recommendations put forward in the current paper will advance the field and increase our understanding of sex- and gender-related mechanisms in the brain and behavior and their relationships to mental health and beyond to better address diversity.…”
Section: Discussionmentioning
confidence: 99%
“…These differences in the service use between the two groups have been replicated by other studies. 12,16 Although the majority of individuals in both groups had been prescribed antipsychotic medications, notably more of the younger patients had been prescribed long-acting depot injection, which tends to reflect poor compliance with treatment and associated high risk. In addition, the use of clozapine was higher in the under-35s.…”
Section: Discussionmentioning
confidence: 99%